Analysis of Process Failures in Plastic Product Manufacturing Using Blow Molding Machines: Analisis Kegagalan Proses Pembuatan Produk Plastik Pada Mesin Blow Molding - Aftian, Muhammad Alriz Nur; Akbar, Ali (Procedia of Engineering and Life Science, 2024)
Abstract. The rapid advancement of technology, particularly in the plastics industry, is closely intertwined with thedevelopment of machinery used in plastic production processes. Commonly used machines in plastic raw materialproduction include blow molding, injection molding, and extrusion. The production cycle time significantly affectsboth the quality and quantity of production. While a faster production cycle may increase the quantity of output, itdoes not necessarily guarantee an improvement in product quality. Hence, it is imperative for companies to identifyfactors leading to production defects to plan controlled improvements. Product quality is a crucial consideration forconsumers when selecting products. PT. XYZ Pasuruan, a manufacturing company specializing in plastic packagingprocessing, faces production issues involving defective products and the underlying factors causing them. Thisresults in time and cost losses due to the need to reproduce faulty products. Therefore, this research aims to developeffective strategies for preventing and reducing production defects. Possible measures include improving productionprocesses, machinery, employee training, or changing raw material suppliers. By addressing the root causes ofthese issues, the industry can enhance product quality, reduce production costs, and increase customer satisfaction..Keywords - Blow Molding Machine; Product Failures; Product Quality